Solar-air drying of eggplant – on the way to waste-free production - V. A. Machulkina; O. P. Kigashpaeva; A. V. Gulin; R. H. Kapanova (Овощи России, 2021)
The growth in the cost of raw materials, vehicles, fuel, incomplete use of the crop leads to an increase in the cost of grown products. As you know, in the process of harvesting and its marketing, about 25-35% are products not sold on time, non-standard products, which are not inferior in nutritional value to the standard and stripping products. Such products are discarded or partially sold by agreement. Processing this part of the crop by solar-air drying is one of the ways to reduce crop losses and make the cultivation technology low-waste and resource-saving.Materials and methods. On the basis of the All-Russian research institute of irrigated vegetable and melon growing – branch of Precaspian agrarian federal scientific center of the Russian academy of sciences (FSBSI “PAFSC RAS”), work was carried out to study the quality of dried eggplants of the institute's selection that were not realized in due time and cleanup collection. For work, they took the fruits of the varieties Nizhnevolzhsky, Panther, Almazny, Astrakom. The goal of the work is to ensure the protection of unsold marketable products, as well as the fruits of the stripping collection from spoilage and obtaining a new product with good nutritional and taste properties, which makes the eggplant growing technology low-waste. Before and after drying, the main chemical substances were determined: the amount of sugars, dry substances, ascorbic acid, nitrates.Results Our results prove that from each ton of unsold products, you can get from 80 to 106 kg of complete dietary products. Ready-made dried eggplants contain, depending on the variety, from 21.17 to 23.86% of the total sugar, the amount of ascorbic acid ranges from 1.63 mg /% to 2.61 mg /%. The amount of nitrates is 7.6-10.2 times less than the permissible (1200 mg / kg) level. Solar-air drying is low-cost, since its storage and transportation requires fewer containers and vehicles. The amount of dried products is reduced to the original, depending on the grade and weight of the loaded raw materials per square meter by 9.4-12.5 times.